Comparing the efficacy of electronic cognitive behavioral therapy to medication and combination therapy for generalized anxiety disorder: a quasi-experimental clinical trial - Stephenson, Callum; Moghimi, Elnaz; Shao, Yijia; Kumar, Anchan; Yee, Caitlin S.; Miller, Shadé; Stefatos, Anthi; Gholamzadehmir, Maedeh; Abbaspour, Zara; Jagayat, Jasleen; Shirazi, Amirhossein; Gizzarelli, Tessa; et al. (Frontiers in Psychiatry, 2023)
Background: Generalized anxiety disorder (GAD) is a debilitating mental health disorder with firstline treatments include cognitive behavioural therapy (CBT) and pharmacotherapy. CBT is costly, time-consuming, and inaccessible. Electronic delivery (e-CBT) is a promising solution to address these barriers. However, due to the novelty of this intervention, more research testing the e-CBT efficacy independently and in conjunction with other treatments is needed. Objective: This study investigated the efficacy of e-CBT compared to and in conjunction with pharmacotherapy for GAD. Methods: This study employed a quasi-experimental design where patients selected their preferred treatment modality. Patients with GAD were enrolled in either e-CBT, medication, or combination arms. The 12week e-CBT program was delivered through a digital platform. The medications followed clinical guidelines. The efficacy of each arm was evaluated using questionnaires measuring depression, anxiety, and stress severity, as well as quality of life. Results: There were no significant differences between arms (N e-CBT = 41; N Medication = 41; N Combination = 33) in the number of weeks completed or baseline scores. All arms showed improvements in anxiety scores after treatment. The medication and combination arms improved depression scores. The e-CBT and Combination arms improved quality of life, and the combination arm improved stress scores. There were no differences between the groups in depression, anxiety, or stress scores post-treatment. However, the combination arm had a significantly larger improvement in quality of life. Gender and treatment arm were not predictors of dropout, whereas younger age was. Conclusions: Incorporating e-CBT on its own or in combination with pharmaceutical interventions is a viable option for treating GAD. Treating GAD with e-CBT or medication appears to offer significant improvements in symptoms, with no meaningful difference between the two. Combining the treatments also offer significant improvements, while not necessarily superior to either independently. The findings suggest that all options are viable. Taking the patient's preferred treatment route based on their lifestyle, personality, and beliefs into account when deciding on treatment should be a priority for care providers.